A Tractable Framework for Option Pricing with Dynamic Market Maker Inventory and Wealth - Fournier, Mathieu; Jacobs, Kris (Journal of Financial and Quantitative Analysis, 2020)
We develop a tractable dynamic model of an index option market maker with limited capital. We solve for the variance risk premium and option prices as a function of the asset dynamics and market maker option holdings and wealth. The market maker absorbs end users’ positive demand and requires a more negative variance risk premium when she incurs losses. We estimate the model using returns, options, and inventory and find that it performs well, especially during the financial crisis. The restrictions imposed by nested existing reduced-form stochastic-volatility models are strongly rejected in favor of the model with a market maker.